Verification of Breast Cancer Treatment Planning with Various Radiation Techniques Using Monte Carlo Simulations and Linac Log Files - Sugandi, R. D.; Azzi, A.; Fadli, M.; Sihono, D. S. K. (Atom Indonesia, 2025)
Due to the complexity of radiotherapy techniques, rigorous Patient-Specific Quality Assurance (PSQA) is crucial to ensure the accuracy of treatment plans. This study aims to evaluate the performance of the Treatment Planning System (TPS) by comparing its dose distribution calculations with those obtained from the PRIMO Monte Carlo simulation. Treatment plans for 3D-CRT, IMRT, and VMAT were generated for a Rando breast phantom using the TPS. Subsequently, the dose distributions from the TPS were compared with those obtained from the PRIMO Monte Carlo simulation. Key metrics, including Homogeneity Index (HI) and Conformity Index (CI), were calculated to assess the quality of dose distribution. Furthermore, the dose constraints on OARs were evaluated to assess the impact on surrounding healthy tissues. To further validate the TPS, dose distributions from the linac log file (Dynalog) for VMAT were reconstructed within the PRIMO environment. These reconstructed distributions were then compared with the dose distributions calculated directly by the TPS. Gamma index analysis was employed to evaluate the agreement between these two sets of data. The comparison between TPS and Monte Carlo simulations revealed that 3D-CRT plans exhibited smaller deviations in HI and CI compared to IMRT and VMAT plans. However, a significant improvement in HI and CI values was observed in both IMRT planning simulations and Dynalog VMAT file simulations, indicating enhanced plan quality. The dose received by OARs in all treatment plans remained within the acceptable dose thresholds, demonstrating effective sparing of surrounding healthy tissues. For the PSQA procedure, the 3D-CRT technique is still the safest due to its lower level of complexity compared to IMRT and VMAT. More complex treatments should consider the robustness of treatment transfer information from TPS to linac to avoid dosimetry errors.